Comparison Of Customary Law In Indonesia And Australia From The Terms Of Customary Rights Of Customary Law Communities - M Najib Ibrahim; Ade Saptomo (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The research aims to analyze and compare aspects of customary rights in the context of customary law in Indonesia and Australia. Customary privileges are an integral part of the life of customary law communities, which include traditional rights to land. This comparison provides in-depth insight into how two countries with different cultural and legal backgrounds manage and protect the ancestral land rights of their customary law communities. This study uses comparative legal procedures to explore the development, protection, and implementation of conventional rights in the two countries. Factors such as the history of colonialism, legislative changes, and local cultural influences play an important role in shaping the legal framework regarding customary rights. This analysis also includes case studies to provide a concrete picture of how traditional liberties are implemented in real situations in customary law communities. The findings of this research can provide a better view of the challenges and opportunities faced by customary law civilizations in defending the sustainability of their customary freedoms amidst the dynamics of modernization and globalization. In addition, this comparison can be a basis for improving policies and a better legal framework to ensure fair and sustainable protection of customary rights for customary law communities in both countries. This analysis presents a cross-cultural understanding of the management of customary rights and the potential integration of traditional law principles in a modern legal context.